Pravni problemi in prostorski podatki - Šumrada, Radoš (Geodetski vestnik, 2002)
This paper presents the general legal provenance, regulatory development and its implementation in the field of GIS technology in Slovenia. The copyright security, privacy protection and liability issues regarding the spatial (geographic) data sets in general are outlined. Further on protection of spatial databases and quality insurance for spatial data in the country of economical and political transition are discussed. The outlined problems are presented in the light of legal provision and its practical acceptance for public services and private enterprises. The main stress is addressed on the spatial data sets produced and maintained by the geodetic service and the surveying branch that are kept in the official databases covering the whole country
Keywords: avtorske pravice; GIS; prostorski podatki; varovanje osebnih podatkov